Desacralization of Myths and Beliefs of Malam Jumat Kliwon by Joni Iskandar - Andina, Dini Lian; Hadiyansyah, Dhuha (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The result show that desacralization occurs when the meaning of values and symbols that were previously considered sacred changes, so that the younger generation gets a new, more relevant understanding. Joni Iskandar portrays the figure of the ghost in this song in a humorous and playful way, removing the fear that usually accompanies Malam Jumat Kliwon. The song manages to ease the tension that often arises in mystical contexts through lyrics that tell the relationship between humans and supernatural beings in a humorous way. The purpose of this research is to study the phenomenon of desacralization in Indonesia’s local cultural traditions, especially those related to Malam Jumat Kliwon, by analyzing the lyrics of a song created by Joni Iskandar. For centuries, Thursday Night of Kliwon historically considered a sacred time with a mysterious aura, has been an important part of Javanese culture. However, the way people see the world this night has started to change along with modernization, urbanization, and the influence of global culture. A descriptive qualitative method is used in this research to study how sacred elements of culture can be desacralized and incorporated into popular culture through the observation of song lyrics.